Development of frozen food Royal Food UMKM - Siregar, Onan M; Selwendri (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2019)
Community service activities aim at increasing the competitiveness of fostered partners in dealing with market developments. The potential of developing frozen food UMKM products is still very open because it is very popular among many people in the City of Medan. Royal Food also experiences the same thing as most UKMKs in Medan, which generally have limited human resource quality of education. The workforce in UKMK is dominated by workers with low education and do not have good financial management and the low utilization of technology. This community service activity was carried out over a period of six months. Activities carried out in the form of socialization and counseling to partners, training in business development and marketing, safe and hygienic production practices and designing more attractive packaging, carrying out production and marketing to partner monitoring and evaluation. After getting a touch of good design, proper management, modernization of production equipment, attractive promotional media, UMKM Royal Food is able to experience business development with increasingly high sales and more competitive products.